DETERMINAN KEUNGGULAN BERSAING DAN PENGARUHNYA TERHADAP EKUITAS MEREK: KASUS PADA INDUSTRI KOSMETIK DI JAKARTA - Elfrida Viesta Napitupulu (Jurnal Komunikasi dan Bisnis, 2018)
The purpose of this study is to explore how the determinants of competitive advantage and its impact to brand equity for cosmetics industry in Jakarta. The result of the research conducted with 400 respondents and 16 research variables which concluded that the determinants of competitive advantage are very significant on cosmetic industries and impact as well to brand equity indicators from cosmetic customersâ€™ perspective. Also the study concludes that there is an influence of brand equity on the competitive advantage for cosmetics industries in Jakarta.Â Keywords: competitive advantage, brand equity, consumer, cosmetics.